Analyzing trends in online learning in higher education in the BRICS countries through bibliometric data - Masalimova, Alfiya R.; Orekhovskaya, Natalia A.; Pivovarov, Vladimir A.; Borovikova, Yana V.; Zhirkova, Galina P.; Chauzova, Vera A. (Frontiers in Education, 2024)
This paper aims to provide a holistic overview of research trends examining online learning in higher education in BRICS countries, an acronym for an association of five major emerging economies: Brazil, Russia, India, China, and South Africa, after COVID-19 using bibliometric analysis. Researchers utilized VOSviewer's software to analyze the data using a bibliometric approach. 971 publications from the SCOPUS database were found appropriate for this research based on the inclusion and exclusion criteria. The results of the number of documents showed that there has been an increase in the amount of research on online learning in higher education in the BRICS countries. Also, the results showed that researchers from China and South Africa had the highest publications on online learning. However, researchers in Russia had very few publications. In addition, the co-authorship relationships among the BRICS countries revealed specific relationships of scholars with their colleagues from other countries. The results revealed that scholars from Indian and South African researchers had close collaborations, and Russian researchers did not have any collaborations with other countries. Finally, the results revealed two lines of research trends. The first line of research has focused on e-learning, online learning, students, and teaching. The second line of COVID-19 has focused on the pandemic, learning, online education, and students. Based on the results, recommendations are made for further research and higher education.